Born in Captivity: The Experiences of Puerto Rican Birth Workers and Their Clients in Quarantine - Reyes, Emaline (Frontiers in Sociology, 2021)
In this article, I seek to understand how the COVID-19 pandemic has impacted childbirth in Puerto Rico, an island that was already in recovery following the occurrence of two devastating hurricanes in the fall of 2017 and a major earthquake in the winter of 2020. Thus, I argue that it is important to discuss not only how individual disasters impact birth, but also how their compounding effects do so. In order to address these research questions, I conducted remote interviews with Puerto Rican birth workers and researchers. During times of crisis, this pandemic included, home and midwife-attended births have become increasingly more popular. However, Puerto Rican midwives and doulas currently have less institutional support than ever. In a time of quarantine when home births are rising, we need to consider whether society is designed to facilitate these models of care. In Puerto Rico, pre-pandemic, there was a less than 1% home birth rate and there still is a lack of legal recognition and protections for homebirth midwives. As this article demonstrates, an acknowledgment of the near-invisible labors of these birth workers is needed, in addition to supplies, support, and protections for them—and not just in times of “crisis.”